2014
DOI: 10.2527/jas.2013-6668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing levels of corn dried distillers grains with solubles and monensin on ruminal biohydrogenation and duodenal flows of fatty acids in beef heifers fed high-grain diets1

Abstract: Corn dried distillers grains with solubles (DDGS) contains high crude fat and is reported to confer to PUFA some degree of protection from ruminal biohydrogenation (BH). There is also indication that inclusion in diets of high energy feed such as DDGS results in a reduced response to monensin in feedlot cattle. This study was conducted to determine the effects of increasing corn DDGS inclusion and monensin on ruminal BH and duodenal flows of fatty acid (FA). Five ruminally and duodenally cannulated Angus heife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, increasing dietary monensin did not alter the fatty acid profile in the PCD muscle in present study, which may be explained by the suggestion of DiLorenzo and Galyean (2010) that high energy density diets are less responsive to monensin addition. In fact, we recently observed that increasing monensin from 28 to 48 mg/kg diet DM in high barley grain diet did not affect ruminal pH and ruminal BH (Xu et al, 2014).…”
Section: Monensin Levelsmentioning
confidence: 88%
“…However, increasing dietary monensin did not alter the fatty acid profile in the PCD muscle in present study, which may be explained by the suggestion of DiLorenzo and Galyean (2010) that high energy density diets are less responsive to monensin addition. In fact, we recently observed that increasing monensin from 28 to 48 mg/kg diet DM in high barley grain diet did not affect ruminal pH and ruminal BH (Xu et al, 2014).…”
Section: Monensin Levelsmentioning
confidence: 88%
“…2 However, similar to unsaturated oils, monensin has also been associated with milk fat depression by inhibiting UFA biohydrogenation within the rumen. 29 The milk fat content and yield were decreased by 15% and 13%, respectively, by monensin supplementation versus control cows in this study. 7 Supplementation of monensin increased significantly the concentration of C18:1 t10, which is considered as a potent inhibitor of milk fat synthesis.…”
Section: Discussionmentioning
confidence: 47%
“…Wood et al (1963) reported that around 33% to 50% of C18:2 is converted to C18:1t. Greater amounts of PUFA and ω6 FAs observed in beef fed DGS when compared to CORN-fed are due to higher levels of C18:1t, C18:1, and C18:2 FAs that usually reach the duodenum when DGS is fed (Vander Pol et al, 2009;Xu et al, 2014). Increased values of those FAs in the lean are due to the high digestibility of fat content in DGS when compared to CORN.…”
Section: Resultsmentioning
confidence: 99%